2014
DOI: 10.1513/annalsats.201306-161mg
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immunity and the Microbiome

Abstract: By definition, the mucosal immune system is responsible for interfacing with the outside world, specifically responding to external threats, of which pathogenic microbes represent a primary challenge. However, it has become apparent that the human host possesses a numerically vast and taxonomically diverse resident microbiota, predominantly in the gut, and also in the airway, genitourinary tract, and skin. The microbiota is generally considered symbiotic, and has been implicated in the regulation of cellular g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 31 publications
2
56
0
1
Order By: Relevance
“…Given the gut microbiota’s diverse role in GI function, enteric immunity [70], endocrinology [11] as well as regulating oxidative stress [71–73] and hydration levels, it is not surprising that efforts to identify the mechanisms by which gut microbiota improves intestinal barrier function of elite athletes are increasing.…”
Section: Main Textmentioning
confidence: 99%
“…Given the gut microbiota’s diverse role in GI function, enteric immunity [70], endocrinology [11] as well as regulating oxidative stress [71–73] and hydration levels, it is not surprising that efforts to identify the mechanisms by which gut microbiota improves intestinal barrier function of elite athletes are increasing.…”
Section: Main Textmentioning
confidence: 99%
“…Complex communities of microbes colonize nearly every epithelial surface of animals, including mucosal epithelial surfaces that become highly valued locales for microbial attachment and growth immediately upon birth (Neish, 2014). The gastrointestinal (GI) system, in particular, has emerged as a prime example of an epithelium-lined organ that sustains an abundant and complex community of closely associated, generally species-specific microbiota, which can exert enormous physiological influence on animal hosts (Savage, 1977; Falk et al, 1998; Neish, 2009; Lozupone et al, 2012; Yatsunenko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…TLR9 was expressed on the colonic apical surface in wild type but not germ-free mice (Ewaschuk et al, 2007). These results demonstrated that the gut microbiota alters the way the host reacts to infectious stimuli or particular bacterial taxa (Neish, 2014) entering the gut, and this difference could also be the case in the present study. Differences in the initial priming of the immune system in the probiotic group are certainly among the potential mechanisms (Thompson et al, 2010;Corthésy et al, 2007).…”
supporting
confidence: 59%